JKN SYARIAH SEBAGAI ASURANSI KESEHATAN DALAM PENURUNAN AKI DAN AKB MENCAPAI MDGS - Sari, Magita Novita; Zulkarnain, Hakim; Hartono, Hartono; As’ari, Asadillah Hadi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
In Indonesia almost 20.000 woman died because of complication in giving birth (Stalker, 2008). Indonesiaâs number of dead mother increase to 359/100.000 women in 2012 (SDKI, 2012). And also Indonesiaâ s number of dead baby is reach 6th in ASEAN (SDKI, 2007). Indonesiaâs number of dead baby is 32/1000 birth (SDKI, 2012). This condition far from MDGâs, which is the number of dead mother 102/100.000 and number of dead baby 23/1.000. One reason in highly increase number is because lack in finance. The government created solution like, Jampersal, Antenatal Care (ANC), and National Health Insurance (JKN). National Health Insurance (JKN) is a must health insurance from government for every Indonesian people. But National Health Insurance JKN aplied the system of conventional insurance which is have a problem, like over usage of country money (APBN) for poor people every month. There is another insurance system, itâ s Syariah Insurance. Itâs growing widely in Indonesia. It shows good development when Indonesiaâs economy grow slower betwen 2000 until 2012 it grows 50% every year. That is the reason why Indonesia need Syariah Health Insurance to give the financial needs in mothersâ health and baby. That is why we found JKN Syariah with Community of Nurse program as the pioneer team in decreasing number of dead mother and number of dead baby. And here we are give solution to solve the problem by our idea JKN Syariah (National Health Insurance with syariah insurance system) as the health Insurance to decrease the number of dead mother and number of dead baby to accomplish MDGs (Milleneum Development Goals) target.Keywords: Number of dead mother, Number of dead baby, Insurance, Syariah.